A comparative study for the effects of synthetic diesel fuels on the performance and emissions of a single cylinder DI diesel engine - Elhemri, Mansour; Reksowardojo, Iman; Wattanavichien, Kanit; Arismunandar, Wiranto (Libyan Journal for Engineering Research, 2017)
The high cost of crude oil, the volatility of the international energy market, the nation energy supply security and the negative environmental impacts have been significantly stimulating the use of alternative fuel in engine applications. The production process of waste cooking oil and waste plastic to diesel-range paraffinic compositions was appropriately proposed according to the conditions of the socioeconomic situations. Two alternative synthetic diesel fuels from waste cooking oil and from waste plastic were successfully manufactured by Biomass R&D Centre of Chulalongkorn University, Saraburi, and had been used in this study. Pyrolysis (thermal cracking) process was implemented to break the long chain hydrocarbons, which is the main composition of waste plastics and waste cooking oil, to diesel range hydrocarbons. The main target of this research is to evaluate the influence of using two synthetic diesels and palm cooking oil biodiesel (palm methyl ester) on the performance, and emissions of a direct-injection single cylinder diesel engine comparing with conventional diesel fuel (CD) as base line. Test bench experiments (constant speed steady state) were conducted with a single cylinder DI CI engine at 1400, 1700 and 2100 rpm, along selected part load. The acquired data was a comparative analysis dealt with: brake specific fuel consumption, brake specific energy consumption, brake thermal efficiency, and exhaust emissions. The knowledge of these comparative results on engine performance obtained in this research can be used to develop high performance green fuels in a near future. The results provided a realistic experimental investigation in terms of using such alternative diesel fuels on diesel engines in Southeast Asian countries.